ANALISIS KEBIJAKAN ALOKASI BELANJA DAERAH KABUPATEN AGAM TAHUN 2024 : DOMINASI BELANJA OPERASI DAN DAMPAKNYA PADA PEMBANGUNAN DAERAH - Frinaldi, Aldri; Pratama, Teddy; Asnil, Asnil; Putri, Nora Eka (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to analyze the expenditure allocation policy of Agam Regency in the Fiscal Year 2024, with a particular focus on the dominance of operational expenditure and its implications for regional development. The 2024 local government budget (APBD) of Agam Regency amounts to approximately IDR 1.67 trillion, of which operational expenditure accounts for IDR 1.30 trillion, or about 77 percent of total spending. Meanwhile, capital expenditure expected to play a strategic role in promoting infrastructure development and improving public services is allocated only IDR 165.78 billion, or around 9.8 percent. This imbalance illustrates the limited fiscal space faced by the regional government in making long-term, productivity-oriented investments essential for stimulating regional economic growth. This research employs a qualitative descriptive method using secondary data sourced from the APBD document of Agam Regency for the 2024 fiscal year. The findings reveal that the dominance of operational expenditure is primarily attributed to the high burden of personnel expenditure, goods and services expenditure, and grants, all of which absorb a substantial portion of fiscal resources. Consequently, this condition restricts the government’s flexibility in allocating funds for capital expenditure that directly supports the development of strategic infrastructure such as roads, irrigation networks, and public facilities. The dominance of operational expenditure has significant implications for regional development, including the slower pace of infrastructure expansion, limited improvement in the quality of public facilities, and reduced government capacity to stimulate productive economic sectors. These conditions highlight the need for a more efficiency-oriented budgeting policy and an increased allocation for capital expenditure. This study recommends strengthening fiscal capacity through the optimization of locally generated revenues (PAD), rationalizing less productive expenditures, and implementing performance-based budgeting to ensure that regional development progresses more effectively, sustainably, and with tangible benefits for public welfare. ABSTRAK Penelitian ini bertujuan untuk menganalisis kebijakan alokasi belanja daerah Kabupaten Agam Tahun Anggaran 2024 dengan menitikberatkan pada dominasi belanja operasi serta implikasinya terhadap pembangunan daerah. Struktur APBD menunjukkan bahwa belanja daerah Kabupaten Agam tahun 2024 mencapai Rp1,67 triliun, dengan porsi belanja operasi sebesar Rp1,30 triliun atau sekitar 77 persen dari total belanja. Sementara itu, belanja modal yang seharusnya berperan penting dalam mendorong pembangunan infrastruktur dan peningkatan layanan publik hanya dialokasikan sebesar Rp165,78 miliar atau sekitar 9,8 persen. Ketimpangan alokasi ini menggambarkan keterbatasan ruang fiskal yang dialami pemerintah daerah dalam melakukan investasi jangka panjang yang berorientasi pada pertumbuhan ekonomi daerah. Penelitian ini menggunakan metode deskriptif kualitatif dengan analisis data sekunder yang bersumber dari dokumen APBD Kabupaten Agam Tahun 2024. Hasil penelitian menunjukkan bahwa dominasi belanja operasi terutama disebabkan oleh tingginya beban belanja pegawai, belanja barang dan jasa, serta belanja hibah, yang secara keseluruhan menyerap sebagian besar sumber daya anggaran. Kondisi ini mengurangi fleksibilitas pemerintah daerah dalam mengalokasikan anggaran untuk belanja modal yang memiliki kontribusi langsung terhadap pembangunan infrastruktur strategis, seperti jalan, jaringan irigasi, dan gedung pelayanan publik. Dampak dominasi belanja operasi terlihat pada terhambatnya percepatan pembangunan daerah, terbatasnya peningkatan kualitas sarana dan prasarana publik, serta rendahnya kemampuan pemerintah daerah dalam mendorong sektor-sektor ekonomi produktif. Situasi tersebut menunjukkan perlunya kebijakan penganggaran yang lebih berorientasi pada efisiensi belanja serta peningkatan proporsi belanja modal. Penelitian ini merekomendasikan perlunya strategi peningkatan kapasitas fiskal melalui optimalisasi PAD, rasionalisasi belanja yang kurang produktif, serta perencanaan anggaran berbasis kinerja agar pembangunan daerah dapat berjalan lebih efektif, berkelanjutan, dan berdampak langsung pada kesejahteraan masyarakat.